Front Cover: N‐Formylation of Amines with CO2 and H2 by Using NHC–Iridium Coordination Assemblies as Solid Molecular Catalysts (Chem. Asian J. 20/2018). Issue 20 (1st October 2018) - Zhang, Yang; Wang, Jiaquan; Zhu, Haibo; Tu, Tao
Abstract : NHC–iridium coordination assemblies have been demonstrated as robust, efficient, and recyclable solid molecular catalysts for N‐formylation of various primary and secondary amines with H2 and CO2 under mild reaction conditions. A number of formamide derivatives could be synthesized in excellent yields even with chiral unprotected amino alcohols as substrates, and with catalyst loadings as low as 0.1 mol %. Furthermore, N, N ‐dimethylformamide could be formed under solvent‐free conditions even at 0.1 mol % catalyst loading. Remarkably, the solid molecular catalyst could be readily reused via simple centrifugation and decantation without any activating treatments. Having no significant loss of activity after 10 runs highlights the potential of this protocol in industry. More information can be found in the Communication by Tao Tu et al. onpage 3018 in Issue 20, 2018 (DOI:10.1002/asia.201800953 ).